A randomized, observer-blind Phase Ib study to identify formulations and vaccine schedules of a trivalent Group B Streptococcus vaccine for use in non-pregnant and pregnant women. Issue 15 (4th April 2016) - Leroux-Roels, Geert; Maes, Cathy; Willekens, Julie; De Boever, Fien; de Rooij, Richard; Martell, Leah; Bedell, Lisa; Wittke, Frederick; Slobod, Karen; Dull, Peter
Abstract: Background: Group B streptococcus (GBS) is a leading cause of sepsis and meningitis in early infancy. Substantial data demonstrate that women with higher levels of circulating antibody against the capsular polysaccharide (CPS) deliver infants at reduced risk of GBS infection, which serves as the basis for vaccine design. This study evaluates two different dosages, two injection schedules and three formulations of an investigational trivalent (serotypes Ia, Ib and III) CRM197 -glycoconjugate GBS vaccine in healthy, non-pregnant women. Methods: 678 healthy non-pregnant women received one or two injections of one of two dosages (5/5/5 μg or 20/20/20 μg) of the investigational vaccine, formulated with or without aluminum hydroxide (Enrolment Group 1), or with full or half dosages of MF59 ® (Enrolment Group 2); or a placebo (Enrolment Groups 1 and 2). Geometric mean serotype-specific antibody concentrations (GMCs) at Days 61 (Enrolment Group 1) and 361 (both Groups) were analyzed to select a formulation suitable for pregnant or non-pregnant women, respectively. Solicited adverse reactions were recorded up to Day 7 and adverse events (AEs) were recorded throughout the study. Results: Rates of reported AEs were similar across all groups. Higher rates of local reactogenicity were seen in adjuvanted vaccine groups compared with non-adjuvanted vaccine (or placebo) groups. All vaccine groups elicited higher GMCs than placebo; differences between treatments were not statistically significant, indicating no additional potential benefit of higher antigen content, addition of adjuvant, or a second dose. Conclusions: All GBS vaccine formulations induced a persistent antibody response and showed similar immunogenicity profiles (NCT01150123 ).